2014
DOI: 10.1128/jvi.00742-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Properties of the Kaposi's Sarcoma-Associated Herpesvirus Latent Origin of Replication That Are Essential for the Efficient Establishment and Maintenance of Intact Plasmids

Abstract: The maintenance of latent Kaposi's sarcoma-associated herpesvirus (KSHV) genomes is mediated in cis by their terminal repeats (TR).Here we show that these many origins provide an essential advantage to KSHV, allowing the DNAs to be maintained without rearrangement. We find also that the correct spacing between KSHV's origins of DNA synthesis is required for them to support synthesis efficiently. The identification of these properties illuminates plasmid replication in mammalian cells and should lead to the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…The related gammaherpesvirus KSHV differs profoundly from EBV. Detailed examinations have shown that the KSHV genome encodes 16 or more sets of replication origins, each located within a copy of its terminal repeats (TRs) and uses one viral protein, LANA1, to bind these origins and mediate their DNA synthesis ( Ballestas et al, 1999 ; Cotter and Robertson, 1999 ; Ballestas and Kaye, 2001 ; Hu et al, 2002 ; Krithivas et al, 2002 ; Barbera et al, 2004 ; Ye et al, 2004 ; Shrestha and Sugden, 2014 ). LANA1 binds these replication origins directly but does not tether them directly to chromosomal DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The related gammaherpesvirus KSHV differs profoundly from EBV. Detailed examinations have shown that the KSHV genome encodes 16 or more sets of replication origins, each located within a copy of its terminal repeats (TRs) and uses one viral protein, LANA1, to bind these origins and mediate their DNA synthesis ( Ballestas et al, 1999 ; Cotter and Robertson, 1999 ; Ballestas and Kaye, 2001 ; Hu et al, 2002 ; Krithivas et al, 2002 ; Barbera et al, 2004 ; Ye et al, 2004 ; Shrestha and Sugden, 2014 ). LANA1 binds these replication origins directly but does not tether them directly to chromosomal DNA.…”
Section: Introductionmentioning
confidence: 99%
“…LANA is dispensable for lytic replication (17)(18)(19). The two essential functions of either protein are to support latent genome replication and to partition the viral plasmid during mitosis to maintain the same genome copy number per cell (20)(21)(22)(23)(24)(25)(26). PELs are dependent on KSHV for survival (27,28).…”
mentioning
confidence: 99%
“…It is likely that there is strong selection for recombination events that lead to a TR number similar to that in the virus. At least 16 TR elements are likely necessary for optimal KSHV episome maintenance (50).…”
Section: Discussionmentioning
confidence: 99%